2012
DOI: 10.1260/1475-472x.11.7-8.885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jet Noise Source Distribution on Acoustic Far-Field Measurements

Abstract: Jet noise production is well known to be of a distributed nature along the jet, with high frequency noise components radiating from locations close to the nozzle exit and low frequency noise being produced farther downstream, around the end of the potential core. Such a distributed source implies that measurements need to be made at a significant distance from the source in order to be in the true geometric (acoustic) far field. The current study presents measurements of fully expanded M j = 1.5 jets operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
3
27
1
Order By: Relevance
“…Spectra that are filtered around higher center frequencies (figure 13 d-/) appear to shift their origins upstream, but never originate from the nozzle exit plane. These findings are in agreement with Kuo et al (2010) who observed that the angular orientation of the lobe of peak intensity remained mostly unchanged with frequency for an unheated Mach 1.5 jet. Contrary to the current result, Kuo et al (2010) observed a broadening of the lobe at higher frequencies and concluded that this was more consistent with the notion that the noise pattern produced by the fine-scale turbulence was omni-directional.…”
Section: Dj)supporting
confidence: 93%
See 2 more Smart Citations
“…Spectra that are filtered around higher center frequencies (figure 13 d-/) appear to shift their origins upstream, but never originate from the nozzle exit plane. These findings are in agreement with Kuo et al (2010) who observed that the angular orientation of the lobe of peak intensity remained mostly unchanged with frequency for an unheated Mach 1.5 jet. Contrary to the current result, Kuo et al (2010) observed a broadening of the lobe at higher frequencies and concluded that this was more consistent with the notion that the noise pattern produced by the fine-scale turbulence was omni-directional.…”
Section: Dj)supporting
confidence: 93%
“…This is caused by a considerable drop in axial phase velocity of the instability waves for low frequencies (St < 0.2) (Troutt & McLaughlin 1982); shallow propagation of low frequency noise was observed in a similar fashion by Kuo et al (2010). For frequencies centered around Stpj = 0.2 in figure 13 (c), the peak radiation angle follows along the Mach wave radiation angle.…”
Section: Dj)mentioning
confidence: 82%
See 1 more Smart Citation
“…This is especially problematic close to the hydrodynamic region where pressure waves comprise a superposition of both acoustic and evanescent signatures [37]. Choosing the wrong path artificially triggers the appearance of nonlinear distortion in the signal that one might interpret as a sign of wave steepening; this problem has been addressed in past studies [2,20]. Here we attempted to place the microphones as close to the jet as possible without them being endangered, and without contaminating the signals with evanescent signatures.…”
Section: Instrumentation and Microphone Placementmentioning
confidence: 99%
“…At low frequencies, figure ' 'a, the peak intensity direction is shallower than <p = 45° and is related to a considerable drop in the axial phase velocity of the instability waves for low frequencies (St < 0.2). 9 Shallow propagation of low frequency noise was also observed by Kuo et al (2010).…”
Section: Iiia Statistics and Spectral Distributionsmentioning
confidence: 88%